2023
DOI: 10.5114/pg.2021.112683
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal symptoms in COVID-19

Abstract: SARS-CoV-2 infection manifests mainly by involving the respiratory system. Due to the presence of abdominal symptoms, the digestive system is clearly involved in the expression, transmission, and possible pathogenesis of COVID-19. There are many theories regarding the development of abdominal symptoms, including angiotensin 2 receptor, cytokine storm, and disturbances of the intestinal microbiome. This paper provides an overview of the most important meta-analyses and publications on gastrointestinal symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…It has been demonstrated that the abundance of Coprobacillus spp., Clostridium ramosum, and Clostridium hathewayiis correlated with the severity of COVID-19, but Faecalibacterium prausnitzii showed an inverse correlation. Bacteroides dorei, Bacteroides thetaiotaomicron, Bacteroides massiliensis, and Bacteroides ovatus, with potentials to reduce angiotensin-2-converting enzyme expression in the gut, were observed to be inversely correlated with the SARS-CoV-2 burden in feces [ 30 ]. However, the heterogeneity of the gut microbiome between unvaccinated and vaccinated individuals remains obscure.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the abundance of Coprobacillus spp., Clostridium ramosum, and Clostridium hathewayiis correlated with the severity of COVID-19, but Faecalibacterium prausnitzii showed an inverse correlation. Bacteroides dorei, Bacteroides thetaiotaomicron, Bacteroides massiliensis, and Bacteroides ovatus, with potentials to reduce angiotensin-2-converting enzyme expression in the gut, were observed to be inversely correlated with the SARS-CoV-2 burden in feces [ 30 ]. However, the heterogeneity of the gut microbiome between unvaccinated and vaccinated individuals remains obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal symptoms, such as nausea, vomiting, loss of appetite, diarrhoea, and abdominal pain, have also been reported (Adhikari et al, 2022; Kariyawasam et al, 2021; Megyeri et al, 2021). Notably, the gastrointestinal tract contains a substantial amount of angiotensin-converting enzyme 2 (ACE-2), a receptor used by SARS-CoV-2 for cell entry (Hamming et al, 2004; Lee et al, 2020; Lewandowski et al, 2023). This allows the virus to infect human enterocytes in the gastrointestinal tract, leading to viral replication and excretion in faeces (Jones et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To carry out seal drainage, opening the lumen of the hollow organs of the gastrointestinal tract is not required [ 12 ]. During opencut drainage, artificial fistulas are formed in the stomach or intestines [ 13 ]. Combined drainage methods combine, at the same time, separate techniques characteristic of closed and open methods [ 14 ].…”
Section: Introductionmentioning
confidence: 99%